Coping with Losses : Options for Disaster Risk Financing in Brazil - World Bank (World Bank, Washington, DC, 2018)
This study presents options for disaster risk financing in Brazil, drawing from international experience. The study presents a series of complementary options for disaster risk financing, based on a preliminary fiscal risk analysis and a preliminary review of the current budget management of natural disasters in Brazil. It benefits from the international experience of the World Bank, which has provided assistance to several countries on the design and implementation ofsovereign disaster risk financing strategies (e.g. Mexico, Colombia, Peru, Indonesia, Vietnam, Philippines, Pakistan and the Caribbean island states). This experience is tailored to the extensive risk profile and institutional, social and economic characteristics of Brazil, as well as to the availability of relevant data.